Diversitas Serangga Permukaan Tanah Pada Pertanian Hortikultura Di Kelurahan Maubeli Kecamatan Kota Kefamenanu - Adriana Korsina Lake; Maria Marselina Bay; Gonsianus Pakaenoni (Fakultas Pertanian, Universitas Timor, 2023)
Soil insects play an important role in the ecosystem, namely in the process of weathering organic matter and their presence and activities have a positive effect on the physical and chemical properties of the soil. Soil insects will break down organic matter and then release it back into the soil in the form of organic matter which is available to green plants and can be an indicator of soil fertility. This study aims to determine the diversity of ground-surface insects in horticultural farming in Maubeli Village, Kota Kefamenanu District, North Central Timor Regency. The research was conducted from January to March 2021. Samples were taken using the Pitfall Trap. Data analysis was carried out using a quantitative method, namely conducting data collection activities, analyzing the data and then identifying it down to the species level. The results showed that there were 633 individual insects belonging to 7 genera, 6 families and 4 orders. The entire insect order found was Hymenoptera, Coleoptera, Orthoptera, and Blattaria. The highest insect diversity was found at night, namely at station I with a Diversity Index value (H') = 5.7204 and at station II with a Diversity Index value (H') = 5.5555. While the Diversity Index value is highest during the day, namely at station II with the Diversity Index (H') = 3.0852.